The Company of Wolves - Gracey, James (Devil's advocates., 2017)
Coinciding with the release of several other classic werewolf films, The Company of Wolves stands apart with its overtly literary roots, feminist stance and art-house leanings. The film's narrative is a puzzle box, unfolding as dreams within dreams and stories within stories, which lead us into the dark woods of the protagonist's psyche. In this book, the author explores these aspects and places the film within the context of the careers of its creators, the history of fairy tales, the representation of the werewolf in literature and cinema and Neil Jordan and Angela Carter's representation of the female Gothic style.